Determinan Volume Pembiayaan Bank Umum Syariah Indonesia - Masudah, Masudah (IKONOMIKA, 2017)
As a financial intermediary institution, Islamic banking should give a financing to deficit units. The aim of this study is to emphasize the factors that had an influence to financing in Islamic banks. This research using panel data regression with 11 Islamic full-pledge banks from 2011 until 2015. The result shows that deposit funds, exchange rate, operational efficiency ratio and interest rate had an impact on Islamic bank’s financing, but other variables such as non-performing financing and inflation doesn't had an impact. From F-test shows that all variables simultaneously had an impact on Islamic bank’s financing. Besides that, the value of adjusted R-square shows that all of the independent variables can explain the model about 78.5%, the others explained by other variables outside the model.